Être Haïtien en Haïti : protestation et appartenance dans les débats sur le Champ de Mars à Port-au-Prince - Nadège Mézié (L'Espace Politique)
On the Champ de Mars, the neuralgic center of power and counter-power of the Haitian capital, a few steps from the national palace and other ministries, street debates are held every day of the week. They bring together between 20 and 200 people, mainly men from the surrounding slums and students. No political party frames these debates, and one can hear opinions from all the political spectrum. The participants discuss, with emphasis, social, political, economic, and religious issues concerning Haiti. Two topics are recurrent that engage both territory and history: sovereignty and the borders of the national community. In the context of acute polymorphous crisis and massive emigration, participants extol a nationalism that rests on the principle of an exclusivist belonging: to be Haitian implies that one must be in Haiti and not dreaming about leaving. Haitian creole is the only language accepted, and credit is given only for those who engage to stay despite “hell.” Heroic figures from the wars of independence, each of them represented by a statue on the Champ de Mars, are exalted. Build on ethnographic fieldwork conducted in 2017, the article examines various levels of territoriality at stake in these public debates (discussion circles, Champ de Mars, Port-au-Prince, Haiti, international) and their articulation with local conceptions (and imaginations) of the national community, its sovereignty, and the meaning of citizenship. The political rhetoric, the relation to space and history, the worries and anger present in these debates, inform us about the lockdown of the country, and the extensive anti-government and anti-corruption demonstrations that took place during 2019.